Lessons Learned from Crisis Management and Amputation Decisions in the Aftermath of High-magnitude Earthquakes in Kahramanmaras on 6 February 2023 - Atilla Orhan (Genel Tıp Dergisi)
Background:Earthquakes of high magnitude and prolonged duration result in catastrophic events, causing significant human and material losses. Immediate medical interventions become crucial in the aftermath of such disasters to prevent long-term disabilities and fatalities. This study focuses on the challenges faced by a volunteer medical team in Kahramanmaras, Turkey, after two major earthquakes struck on February 6, 2023, affecting millions of people. Methods:A team of 35 experienced medical professionals, led by a cardiothoracic surgeon, was dispatched to the disaster site. The team's schedule, tasks, and logistical details were organized to optimize their response. The study outlines the methods employed by the team to assess and treat extremity traumas, including amputations, during the first-week post-earthquake. Results:The earthquake severely impacted local healthcare facilities, resulting in inadequate patient management, insufficient medical personnel, and logistical difficulties. The volunteer team worked tirelessly, performing surgeries and amputations and providing medical equipment. A total of 16 lower limb amputations and two upper limb amputations were performed due to severe extremity crush injuries. Discussion:The chaotic conditions post-earthquake revealed challenges in managing crush syndrome patients. The study discusses the decision-making process for amputations, fasciotomies, and patient transfers. Despite limited facilities, the team restored the hospital to full functionality within a few days. Conclusion:The study concludes that volunteer healthcare teams are crucial in disaster response. Effective organization, communication, and logistics are essential for optimal performance. Continuous training on disaster scenarios for volunteer teams is recommended. The importance of restoring healthcare facilities to routine operation after immediate crisis response is emphasized, as well as the need for comprehensive scientific data to understand the extent of the disaster's impact.